Сохранить свое, не пренебрегая чужим: Культурные коды детской литературы Русской эмиграции [To Preserve Our Own Without Neglecting the Foreign: Russian Émigré Children’s Literature Cultural Codes] - Demidova, Olga (Slavica Revalensia, 2019)
The article treats the problem of the “own” and the “foreign” in culture, applying it to the history of Russian first-wave emigration in general and its children’s literature, in particular. Relying on the comparative analysis of various émigré cultural discourses and their hermeneutic reading as the methodology, as well as the vast number of sources (émigré periodicals of various ideological, aesthetic, and artistic orientation, émigré writers’ and prominent cultural figures’ memoirs), the author reconstructs the history and formal / functional paradigms of children’s literature (also understood as literature for children’s and / or familyreading) during the emigration of the 1920s–1930s.Two major theoretical issues discussed in the article are the formation of the mechanisms of the cultural / literary canon amid the changed existential circumstances, and the functional shift of children’s’ literature during the diaspora towards the pedagogical rather than the aesthetic or the artistic.The undertaken analysis makes it possible to argue that the children’s’ literature canon during emigration a) preserved the traditional Russian classical literary canon, b) enriched it by means of including quite a few names and titles formerly considered “trivial”, c) included a number of “texts for children” written in exile as well as memoirs of the “good olden times” in the lost / abandoned  motherland, d) made use of children’s books by foreign authors translated into Russian both before and during the exile period.